The Effects of different binders on mechanical properties of asphalt concrete 14 - Liew, Yee Shian, 1988-; Haryati Yaacob; Fakulti Kejuruteraan Awam (2012)
Project Paper (Sarjana Muda (Awam - Pengangkutan dan Jalanraya)) - Universiti Teknologi Malaysia, 2012